Fiserv takes on the e-billing market : how can we get them to turn off paper? - Grayson, Kent, (SAGE Knowledge. Cases., 2017)
Fiserv, a pioneer in electronic payments, would like to increase the number of consumers who receive bills electronically. Currently, adoption is relatively low. To help guide their efforts, Fiserv managers have done extensive customer research and have segmented the market based on customer perceptions of e-billing. Students must recommend which segments to target and why. To support their recommendations, students must calculate the likely financial costs and benefits of adoption, estimate the likely returns for targeting different segments, and make targeting and positioning recommendations based on these calculations. Because Fiservs direct customers are billers (such as utilities and credit card companies) and its end users are individual consumers, the case allows a focus on both B2B and B2C issues.